Dinâmicas comunicacionais no processo criativo de design de produto: característica e construção da linguagem a partir dos painéis semânticos - Farias, Marcelo José Oliveira de (2013)
The communicational function that industrial products have through non-verbal language determines the interest process which may have a functional or emotional point of view from the observer. Besides a technical and creative feature, design is also responsible for the configuration of products. Design means a signification process from the organization of signals in a structure made of codes which characterizes the language and the message of a product. The language system is necessary for design so that this communication between the observer and the message of the product will be established. From this perspective, can we consider the visual techniques used in the creation process, such as conceptual or semantic panels, responsible to determine the language and message of industrial products? From the fundamental question of the object of study, other questions come up and certainly help the basis necessary to limit this research. (1) How are the signal systems, which form the design language of the product, constructed and organized? (2) Which rules guide the definition of this language in the creation process? And (3) Which are the communicational dynamics set from the visual and semantic panels? This study, thus, is based on the analysis of conceptual and semantic panels developed in the creation process of three industrial design offices: Domus Design, Questto|Nó and Design Connection. In this piece of work the creation process is taken as intellectual and sensitive, described as a fallible process with tendency, sustained by the uncertainty logics and involving random intervention. It also opens up for the introduction of new ideas. The theoretical basis of this research is oriented by the process criticism developed by PhD Cecília Salles, which merges with a theoretical board of design represented by Bernhard Burdek, Gui Bonsiepe, Mike Baxtere Rafael Cardoso, as well as communication and semiotics field by Edgar Morin, Lucia Leão,Lucrécia Ferrara and Santaella